PENGUNGKAPAN EMISI KARBON: MEMAHAMI PERAN PROFITABILITAS, GENDER DEWAN, DAN MEDIA EXPOSURE: CARBON EMISSION DISCLOSURE: UNDERSTANDING THE ROLE OF PROFITABILITY, BOARD GENDER, AND MEDIA EXPOSURE - Putri, Nurul Hikmah; Savitri, Enni; Silfi, Alfiati (Universitas Riau, 2025)
In Indonesia, corporations are now required to disclose their carbon emissions voluntarily, mostly to lower risk and acquire credibility. Accounting rules govern the reporting of carbon emissions, which is a crucial component of corporate social responsibility. Since the energy industry contributes significantly to emissions and is crucial to economic growth, it also confronts environmental problems as a result of overexploitation, underscoring the need for open disclosure of carbon emissions. With environmental performance serving as a moderating variable, this quantitative study intends to investigate the impact of media exposure, board gender, and profitability on carbon emissions disclosure in energy sector businesses listed on the Indonesia Stock Exchange between 2019 and 2023. Panel data regression models on STATA were used for both descriptive and inferential statistical analysis of the study data. The findings indicate that carbon emissions disclosure is positively impacted by media exposure, profitability, and the gender of the board of directors and commissioners. Environmental performance successfully moderates this link. The results suggest that in order to increase environmental responsibility and transparency, businesses should give priority to these three factors